2011
DOI: 10.1371/journal.pone.0028117
|View full text |Cite
|
Sign up to set email alerts
|

Both hMutSα and hMutSß DNA Mismatch Repair Complexes Participate in 5-Fluorouracil Cytotoxicity

Abstract: BackgroundPatients with advanced microsatellite unstable colorectal cancers do not show a survival benefit from 5-fluorouracil (5-FU)-based chemotherapy. We and others have shown that the DNA mismatch repair (MMR) complex hMutSα binds 5-FU incorporated into DNA. Although hMutSß is known to interact with interstrand crosslinks (ICLs) induced by drugs such as cisplatin and psoralen, it has not been demonstrated to interact with 5-FU incorporated into DNA. Our aim was to examine if hMutSß plays a role in 5-FU rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Although MSS patients showed a benefit from 5-FU treatment, MSI patients did not (46), a finding confirmed in smaller follow-up studies (47,48). Laboratory-based investigations have suggested that components of the MMR machinery bind to 5-FU incorporated DNA, raising the possibility that they mediate the observed cytotoxic response (49,50). Further clinical studies have generally substantiated the finding that MSI patients do not benefit from 5-FU therapy, with some exceptions (51).…”
Section: Prognostication and Predictionmentioning
confidence: 90%
“…Although MSS patients showed a benefit from 5-FU treatment, MSI patients did not (46), a finding confirmed in smaller follow-up studies (47,48). Laboratory-based investigations have suggested that components of the MMR machinery bind to 5-FU incorporated DNA, raising the possibility that they mediate the observed cytotoxic response (49,50). Further clinical studies have generally substantiated the finding that MSI patients do not benefit from 5-FU therapy, with some exceptions (51).…”
Section: Prognostication and Predictionmentioning
confidence: 90%
“…The MMR recognition complexes recognize and bind to ingested or parenteral 5-fluorouracil (5FU) and are then converted and incorporated into DNA. Both MSH2-MSH6 and MSH2-MSH3 complexes can bind 5FU within DNA and trigger cell death [5257]. When the MMR recognition complexes are not present, cell death does not occur and cells may proceed with mitosis with 5FU-induced and other novel mutations contained within DNA.…”
Section: Msi and Modification Of Treatment Approaches For Patients Wimentioning
confidence: 99%
“…We later showed that this had an effect on patient survival from colorectal cancer, as patients with a defective DNA mismatch repair system did not show a survival benefit with adjuvant 5-FU treatment [10]. We worked out the mechanism, showing that individual complexes from DNA mismatch repair had specific binding affinities for 5-FU incorporated into DNA [11, 12] and that isolating the DNA component of 5-FU (from the RNA component) proved that DNA mismatch repair could trigger cell death once it recognizes 5-FU [13]. Talented postdocs Akihiro Tajima, Moriya Iwaizumi, and Yasushi Hamaya [14] were key in figuring out this important process.…”
Section: University Of California San Diegomentioning
confidence: 99%